Comparative Assessment of Total Antioxidant Capacity of Unstimulated Saliva Which Can Reflect the Oxidative Stress between Autism Children and Normal Children - Sundaram Manikandan; Kumarasamy Baskaran; Subbian Kavitha P; Perumal Mohan Kumar; Balu Kiruthika (Wolters Kluwer Medknow Publications, 2024)
AimTo assess the level of total antioxidant capacity (TAC) in the unstimulated saliva of autism children and normal children. MethodsA total of 60 children participated in the study (autism children-30; normal children-30) in the age-group of 7-14 years, at a Special Needs Children's Home in Salem district. Both groups were further subdivided into subgroups of 15 children each (caries-free and caries-active). All children were given instructions regarding saliva sample collection, and unstimulated saliva samples were collected in sterile cryovials and transported to the laboratory at 4°C, where the TAC of saliva was evaluated using the spectrophotometric assay. ResultsTAC of autism children was comparable to that of normal children due to personal care and improved diet. TAC was increased in caries-active children when compared to caries-free children in both groups. When comparing the mean values of TAC in caries-active and caries-free children of both groups, it was not statistically significant. So, from the above results, it can be assumed that the diet, age, and caries activity have a definitive influence on the TAC level of saliva. ConclusionPersonal hygiene, diet, age, and caries activity have a definitive influence on the level of TAC in saliva.